2020
DOI: 10.1016/j.phro.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A study of the clinical, treatment planning and dosimetric feasibility of dose painting in external beam radiotherapy of prostate cancer

Abstract: Background and purpose: Radiotherapy dose painting is a promising technique which enables dose escalation to areas of higher tumour cell density within the prostate which are associated with radioresistance, known as dominant intraprostatic lesions (DILs). The aim of this study was to determine factors affecting the feasibility of radiotherapy dose painting in patients with high and intermediate risk prostate cancer. Materials & Methods: Twenty patients were recruited into the study for imaging using a 3 T mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…One of the leading reasons for the focal boost approach not being feasible was in instances of overlap between the boost volume and OARs. In the research undertaken by Blake et al [60], the boost volume of 83% of patients overlapped with surrounding OARs. In 42% of patients, the intended boost dose of 86 Gy was limited due to the overlap between the boost volume and the urethra.…”
Section: Dose-limiting Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the leading reasons for the focal boost approach not being feasible was in instances of overlap between the boost volume and OARs. In the research undertaken by Blake et al [60], the boost volume of 83% of patients overlapped with surrounding OARs. In 42% of patients, the intended boost dose of 86 Gy was limited due to the overlap between the boost volume and the urethra.…”
Section: Dose-limiting Factorsmentioning
confidence: 99%
“…The longest reported follow-up time was 124 months [49]. In the planning studies, as shown in Table 2, the majority of studies utilized mpMRI for GTV delineation [10,18,45,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. Five studies utilized PET-CT [12,[76][77][78][79][80], and four studies used "other methods" such as histopathology data or hypothetical IPLs [81][82][83][84].…”
Section: Statistics Of Reviewed Studiesmentioning
confidence: 99%
“…The dose redistribution can also be achieved by dose escalation to the detected IPLs. Boosting IPLs without violating the dose constrains of OARs has been shown to be feasible, [59][60][61] and an increased tumor control relative to uniform dose prescription has been reported. 38 However, the undetected lesions or the uncertainty in delineating IPLs from MRI or PET images 62 may lead to underdosing of sub-volumes of the prostate.…”
Section: Similar Studiesmentioning
confidence: 99%
“…Ling et al 1 introduced the concept of a biological target volume (BTV) and proposed the idea of delivering radiation dose distributions based on functional sub-volumes within a target. This has led to multiple studies introducing the concept of a "boost volume" in prostate cancer (PCa) radiotherapy, [2][3][4][5][6][7] whereby a sub-region within the prostate gland is defined to receive an escalated dose of radiation whilst preserving standard doses to the remaining target to minimize risk of increased toxicity. In current standard boost-dose strategies,there is no deliberate attempt to vary the dose distribution through the boost volume, however, in practice, a non-uniform distribution arises as a result of dose gradients generated in an attempt to maintain dose to organs at risk below threshold levels.…”
Section: Introductionmentioning
confidence: 99%